The Development of Prospective Music Teachers’ Harmonic Hearing at Higher Education Establishments - Zavadska, Galina; Davidova, Jelena (Pedagogika, 2015)
The development of harmonic hearing is an essential component of the system of music teachers’ training. The paper is concerned with the type of a case study which deals with the study of professional groups (a bigger and more diffusive group of 14 students). The process of training music teachers at sol-fa classes in a higher education establishment is analyzed and described. The sol-fa classes are oriented towards the development of harmonic hearing. The purpose of the study is to develop a technology of conducting sol-fa classes oriented towards developing students’ – the prospective music teachers’ – harmonic hearing on the basis of a case-study methodology; to present the developed material and ways of its application in the training process; to analyze and summarize the results of the research done. The research results show that the criteria relating to practical music making of students, such as polyphonic singing and intoning intervals and chords, and also those relating to creativeness, such as improvisation and composing the accompaniment for the melody, have been the most effective ones.